(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: In the recent years C. albicans has been identified by researchers for having an important role in cariogenicity along with bacteria like S. mutans and lactobacilli, attributing to its acidogenic, aciduric and hetero-fermentive properties. Objective: The present study evaluated the frequency, intensity, and species of oral Candidal carriage in children with primary and mixed dentition and to identify the association between oral Candidal carriage in children and dental caries. Participants: 100 healthy children of age groups: group A: 4-7 years; and group B: 8-12 years, both caries active (divided into dmf/dmf+DMFT index 1-5, 6-10 and >10) and caries free were randomly selected for the study. Study design: After a detailed intraoral examination, swab samples were taken from tongue and carious lesion for mycological examinations isolate Candida from their oral cavities in order to study the Candidal carriage in children with and without dental caries. Results: Candidal carriage among children with high caries index was significantly higher that caries free children. 92.86% of the children from group A (4-7 years) having dmf index > 10 and 76.93% from group B (8-12 years) having dmf + DMFT index > 10 showed positive candidal carriage. Also, carriage of non albicans species of Candida increased with age. Conclusion: The present study suggests a strong relation between Canddial carriage and dental caries in children. Further work needs to be done on larger samples recruited in community-based settings to substantiate the association of oral Candidal carriage with dental caries.